Understanding the educational inequalities in suicide attempts and their mediators: a Mendelian randomisation study - Jing Wang; Ye Yang; Rui Gao; Lilu Ding; Jiahao Zhu; Dan Zhou; Yingjun Li; Houpu Liu (General Psychiatry)
Background Educational inequalities in suicide have become increasingly prominent over the past decade. Elucidating modifiable risk factors that serve as intermediaries in the impact of low educational attainment on suicide has the potential to reduce health disparities.Aims To examine the risk factors that mediate the relationship between educational attainment and suicide attempts and quantify their contributions to the mediation effect.Methods We conducted a two-sample Mendelian randomisation (MR) analysis to estimate the causal effect of educational attainment on suicide attempts, utilising genome-wide association study summary statistics from the Integrative Psychiatric Research (iPSYCH; 6024 cases and 44 240 controls) and FinnGen (8978 cases and 368 299 controls). We systematically evaluated 42 putative mediators within the causal pathway connecting reduced educational attainment to suicide attempts and employed two-step and multivariable MR to quantify the proportion of the mediated effect.Results In the combined analysis of iPSYCH and FinnGen, each standard deviation (SD) decrease in genetically predicted educational attainment (equating to 3.4 years of education) was associated with a 105% higher risk of suicide attempts (odds ratio (OR): 2.05; 95% confidence interval (CI): 1.81 to 2.31). Of the 42 risk factors analysed, the two-step MR identified five factors that mediated the association between educational attainment and suicide attempts. The respective proportions of mediation were 47% (95% CI: 29% to 66%) for smoking behaviour, 36% (95% CI: 0% to 84%) for chronic pain, 49% (95% CI: 36% to 61%) for depression, 35% (95% CI: 12% to 59%) for anxiety and 26% (95% CI: 18% to 34%) for insomnia. Multivariable MR implicated these five mediators collectively, accounting for 68% (95% CI: 40% to 96%) of the total effect.Conclusions This study identified smoking, chronic pain and mental disorders as primary intervention targets for attenuating suicide risk attributable to lower educational levels in the European population.